Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper on Denmark underlies estimates of inefficiencies in the goods and labor markets. The IMF's new macroeconomic model, the global economic model (GEM), has been used to provide estimates of the impact of successfully implementing the European Council's ambitious Lisbon reform agenda. GEM incorporates markups in the goods and labor markets that are summary measures of the net impact of all the regulatory structures in an economy. The euro area goods market reform in the service sector is twice that required in Denmark, the euro area must also increase competition in manufacturing.